Neolinocarpon penniseti sp. nov. on the grass Pennisetum purpureum (Poaceae) - Bhilabutra W. (2014)
Neolinocarpon penniseti sp. nov. is described from the grass Pennisetum purpureum collected in Hong Kong. This is the only Neolinocarpon species found on a non-Arecaceous host. The species has shorter ascospores than the other species in the genus. A key to species of Neolinocarpon is provided. © 2006 Adac. Tous droits réservés.